Transient hypersensitivity to soybean meal in the early-weaned pig - D F Li; G Reddy; Frank Blecha; Joe D Hancock; G Allee; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1988)
An experiment was conducted to determine if baby pigs develop intestinal hypersensitivity to dietary soy protein. Challenging nursery pigs with soybean meal following oral infusion of soybean meal from day 7 to day 14 of age resulted in villus atrophy and lower average daily gain by 28 days of age. At 56 days of age, there were no differences in weight gains between pigs fed soy protein and pigs fed milk protein. Pigs exposed to soybean meal before weaning had increased anti-soybean protein immnoglobulin titers at 4 wk (7.2 vs 4.0) and at 8 wk (7.6 vs 4.2). Thus, challenging baby pigs with soybean meal followed by feeding soybean meal resulted in an immune response as indicated by transient hypersensitivity at 4 wk and increased anti-soy protein titers. Also, growth was temporarily decreased at 4 weeks, but increased at 8 weeks.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Early weaned pigs; Soybean protein; Villus; Crypt; Hypersensitivity